SYNERGISTIC EFFECTS OF FINANCIAL LITERACY EDUCATION AND FINTECH TOOLS ON SUSTAINABLE INVESTMENT BEHAVIOUR IN CHINA - Ooi Kok Loang; Cao Lei (International Journal of Accounting, Finance and Business, 2023)
This study explores the role of financial literacy education and fintech tools in promoting sustainable investment behaviour in the context of green investment. Using a qualitative research approach, in-depth interviews were conducted with 30 individual investors from Shanghai and Beijing. The study findings suggest that financial literacy education and fintech tools have a positive impact on promoting sustainable investment behaviour. The use of fintech tools such as robo-advisors and social media platforms can increase the accessibility of green investment information and enable investors to make informed investment decisions. Financial literacy education can also increase investors' knowledge and understanding of sustainable investments. However, the study also highlights significant challenges related to the effectiveness of financial literacy education and Fintech in promoting sustainable investment behaviour, including information asymmetry, lack of access to technology, and behavioral biases among individual investors. The study contributes to the existing literature on sustainable investment behaviour by providing insights into the role of financial literacy education and fintech tools in promoting sustainable investment behaviour in green investment. The findings of this study have implications for practitioners, policymakers, and researchers seeking to promote sustainable investment behaviour in the context of green investment.